Leadership Development of Doctoral Students in a Carnegie Project on the Education Doctorate Affiliated Ed.D. Program - Barker, Nan; Ayala, Daniel R. (Educational (Re)naissance, 2017)
Educational practitioners in the 21st century must respond to the availability of a wide array of data relating to student outcomes and student achievement. To make effective use of this data as well as be able to respond to the growing needs of the field, educational practitioners must be able to apply the knowledge they gain in the graduate preparation programs. In this article, the authors reflect on the role of a signature pedagogy grounded on inquiry-based learning in their leadership development, and how an ongoing emphasis on action research throughout their doctoral program was invaluable in their professional and academic growth. As a result, the authors recommend that action research should strongly supplement traditional, theory-driven graduate pedagogy in education.